Pembagian Hasil Migas Melalui Cost Recovery Dan Gross Split Bagi Sebesar-Besarnya Kemakmuran Rakyat Menurut UUD NRI Tahun 1945 - Farhani, Athari; Azizah, Faiqah Nur; Usadhani, Panggalih; Kurniawan, Faridh (Jurnal Hukum & Pembangunan, 2022)
Indonesia is a country with abundant natural resources. In oil and gas, two models of product sharing contract are known, namely through cost recovery and gross split. Through Permen of ESDM Number 12 of 2020 concerning the Third Amendment to Regulation of the Minister of Energy and Mineral Resources Number 8 of 2017 concerning Gross Split Production Sharing Contracts, which through this regulation the government makes it easy for contractor entrepreneurs to choose the Gross Split and Cost Recovery model schemes. Meanwhile, the 1945 Constitution of the Republic of Indonesia has outlined that natural resources are controlled by the state and used to the greatest extent for the prosperity and welfare of the Indonesian people.